2011
DOI: 10.1159/000321911
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Safety of Granulocyte-Monocyte Adsorption Apheresis for Patients with Ulcerative Colitis Positive for Cytomegalovirus in Comparison with Immunosuppressants

Abstract: Background: Cytomegalovirus (CMV) infection exacerbates ulcerative colitis (UC) refractory to immunosuppressive therapies (IMT). However, the underlying UC remained active in some UC patients, despite the fact that CMV-DNA in colonic mucosa became negative after antiviral therapy. Therefore, new therapeutic strategies for UC patients concomitant with CMV infection in mucosa are required. Aims: The aim of this study was to evaluate the effect and safety of granulocyte-monocyte adsorption apheresis (GMA) in UC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…In fact, Yoshino et al reported that GMAA did not induce colonic CMV reactivation in UC patients with a history of CMV infection. 22 In the present study, the clinical remission rate and mucosal healing following intensive GMAA did not differ significantly between UC patients positive for CMV and UC patients negative for CMV. A similar tendency was observed for the mucosal healing ratio.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In fact, Yoshino et al reported that GMAA did not induce colonic CMV reactivation in UC patients with a history of CMV infection. 22 In the present study, the clinical remission rate and mucosal healing following intensive GMAA did not differ significantly between UC patients positive for CMV and UC patients negative for CMV. A similar tendency was observed for the mucosal healing ratio.…”
Section: Discussioncontrasting
confidence: 43%
“…[19][20][21] Furthermore, it was recently reported that GMAA could be safe for UC patients with a history of CMV infection due to the avoidance of colonic CMV reactivation compared with UC patients treated with immunosuppressive drugs. 22 Theoretically, GMAA removes granulocytes and monocytes/macrophages, where CMV infection is latent and reactivates. GMAA does not affect colonic CMV reactivation.…”
mentioning
confidence: 99%
“…Also, current clinical and experimental data demonstrate that insufficient control of inflammation could result in the exacerbation of UC disease activity with the induction of HCMV reactivation. 2,3 In fact, our previous report demonstrated that 26% of UC patients positive for HCMV-DNA in colonic tissue achieved clinical remission with anti-viral treatment, and the remainder required anti-inflammatory treatments without affecting HCMV reactivation, even after elimination of HCMV in colonic tissue. 2 It must be kept in mind that optimal control of colonic inflammation should be done in cases of UC patients positive for HCMV who are refractory to conventional immunosuppressive therapies.…”
mentioning
confidence: 99%
“…2,3 In fact, our previous report demonstrated that 26% of UC patients positive for HCMV-DNA in colonic tissue achieved clinical remission with anti-viral treatment, and the remainder required anti-inflammatory treatments without affecting HCMV reactivation, even after elimination of HCMV in colonic tissue. 2 It must be kept in mind that optimal control of colonic inflammation should be done in cases of UC patients positive for HCMV who are refractory to conventional immunosuppressive therapies. Therefore, we consider that to only focus the therapeutic effect of anti-viral treatment on active UC patients with HCMV reactivation is not favourable.…”
mentioning
confidence: 99%
“…In the study by Yoshino et al [4] presented in this journal, 64 patients with ulcerative colitis refractory to immunosuppressive therapies (such as steroids and immunomodulators) were retrospectively enrolled and the clinical outcomes of GMA and immunosuppressive therapy after 2 weeks of ganciclovir treatment were investigated. The total colectomy rate in ulcerative colitis patients positive for CMV was 36%.…”
mentioning
confidence: 99%